THE INFLUENCE OF THE BABY-FRIENDLY HOSPITAL INITIATIVE ON BREASTFEEDING OUTCOMES - Handriani, Egha; Huriah, Titih (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2023)
The World Health Organization has recommended babies be breastfed exclusively during the first six months of life and continue with complementary foods until the age of 2 years. However, the average data on the number of exclusive breastfeeding coverage in the world has only reached 38%, still far below the target of at least 50%. One of the WHO programs to increase exclusive breastfeeding since 1991 is the Baby-Friendly Hospital Initiative (BFHI). The literature review aims to find out the Effect of the Infant-Friendly Hospital Initiative on breastfeeding outcomes. The literature review follows the PRISMA reporting method. The database uses PubMed, Science Direct, EBSCO, Google Scholar, Scopus and Pro-quest. The key word is Baby OR baby newborn AND baby-friendly OR baby-friendly hospital initiative OR BFHI AND breastfeeding outcomes OR breastfeeding OR breastfeeding production. The inclusion criteria are the articles of the last five years (2017-2022), English-language, Full-text, and research in breastfeeding outcomes. The exclusion criterion is a review of only abstracts and books. JBI is used as a tool for evaluating the quality of research journals. Systematic analysis is used for synthesis results. The results showed that babies who were breastfed in the first 48 hours of delivery and did not give pacifiers or bottles had a low risk of not giving exclusive breastfeeding. The Baby-Friendly Hospital Initiative (BFHI) can improve breastfeeding in children before the age of six months.